Improving student in-depth understanding of statistics - Ograjenšek, Irena (Metodološki zvezki, 2007)
When striving to improve student in-depth understanding of statistics, one of the most important challenges instructors face is overcoming the negative student attitude towards statistics. This paper focuses on one approach that has been very effective, namely the inclusion of historical insights into statistics courses. Possibilities of doing that are numerous and range from simple exercises (e.g. assigning a face to the name, or discussing examples of famous past statistical achievements and blunders) to well-rounded lectures (e.g. on socio-economic context of past developments in statistics and methodology, or the role of women in statistics). In the paper, the advantages and disadvantages of this approach are discussed in detail along with several excellent resources that can aid instructors in their endeavours to give statistics a more human face in the eyes of their students.
Keywords: Statistics; Statistika; Students; Študentje; Teaching; Poučevanje; Slovenia; Slovenija; študenti; student; metodika pouka; pristop